RETROSPECTIVE ANALYSIS OF IMMUNOGENIC CELLS AMONGST COVID-19 PATIENTS FROM TERTIARY CAREHOSPITALS OF PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Background: The co-relation between lymphocytes and neutrophils is significant in COVID-19 patients. Change in blood composition is the major risk in COVID-19 patients. Arterial blood is the medium to transport nutrients to cells and take away wastes from cells. We have conducted this retrospective cohort study to find correlation between blood components in COVID-19 patients.Methods: The reports collected from COVID-19 ward in various tertiary care hospitals of Lahore included 60 patients of which 32 male and 28 female. The median age of the patients is 55 (32-81). All these patients show huge difference in the components of peripheral white blood cells among lymphocytes and neutrophils.Results: The reports show the changes in neutrophils in 6 patients are in range of 60-70 of, 14 patients are in 71-80 and the rest of 37 patients are above from 80. The lymphocyte ratio in 33 patients is below the 15, 26 patients are in the range of 15-30 and 2 patients onlyhave 31-40 of total WBCs.Conclusion: Hence, the results of data collected from Pakistan population also have similar case in all the patients of COVID-19 that have suffered with low level of lymphocytes and higher level of neutrophils. However, the early signals of disease development indicated by peripheral white blood cells and can be chosen as an effective parameter for the treatment of COVID-19.